Taurine and its analogs in neurological disorders: Focus on therapeutic potential and molecular mechanisms - Jakaria, Md. (Redox Biol, 2019)
Taurine is a sulfur-containing amino acid and known as semi-essential in mammals and is produced chiefly by the liver and kidney. It presents in different organs, including retina, brain, heart and placenta and demonstrates extensive physiological activities within the body. In the several disease models, it attenuates inflammation- and oxidative stress-mediated injuries. Taurine also modulates ER stress, Ca(2+) homeostasis and neuronal activity at the molecular level as part of its broader roles. Different cellular processes such as energy metabolism, gene expression, osmosis and quality control of protein are regulated by taurine. In addition, taurine displays potential ameliorating effects against different neurological disorders such as neurodegenerative diseases, stroke, epilepsy and diabetic neuropathy and protects against injuries and toxicities of the nervous system. Several findings demonstrate its therapeutic role against neurodevelopmental disorders, including Angelman syndrome, Fragile X syndrome, sleep-wake disorders, neural tube defects and attention-deficit hyperactivity disorder. Considering current biopharmaceutical limitations, developing novel delivery approaches and new derivatives and precursors of taurine may be an attractive option for treating neurological disorders. Herein, we present an overview on the therapeutic potential of taurine against neurological disorders and highlight clinical studies and its molecular mechanistic roles. This article also addresses the neuropharmacological potential of taurine analogs.